Roles of telocytes dominated cell-cell communication in fibroproliferative acute respiratory distress syndrome - Yonghua Zheng; Songshan Cai; Zongfeng Zhao; Xiangdong Wang; Lihua Dai; Dongli Song (Wiley, 2024)
Abstract Telocytes (TCs) are a new type of interstitial cell identified in multiple tissues of mammals, including the human lung, and mediate homocellular or heterocellular cell‐cell communication. Acute respiratory distress syndrome (ARDS) is characterized by acute hypoxemia respiratory failure and combined with direct and indirect lung injury, which is induced by pneumonia, sepsis, burns, etc. Pulmonary fibrosis is a progressive lung disease that occurs due to increased fibrosis of lung tissue in response to chronic injury of the epithelium and gets more and more attention as a well‐recognized sequela of ARDS or mechanical ventilation. However, the existing intervention measures could not prevent the progression of pulmonary fibrosis. Although the protective effect of TCs in acute lung injury had been demonstrated in both cellular and animal models in previous studies by our or other researchers, the roles of TCs mediated cell‐cell communication in fibroproliferative ARDS is unclear. This review is aimed at integrating our understanding of TC‐mediated cell-cell communication in lung diseases with pulmonary fibrosis after ARDS.